2013
DOI: 10.1021/ja405128k
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Transcriptional Regulators inChaetomium globosumActivates Biosynthetic Pathways and Reveals Transcriptional Regulator-Like Behavior of Aureonitol

Abstract: Postgenomic analysis revealed that many microorganisms carry numerous secondary metabolite biosynthetic genes on their genome. However, activities of those putative genes are not clearly reflected in the metabolic profile of the microorganisms, especially in fungi. A recent genome mining effort is promising in discovering new natural products. However, many fungi and other organisms are not amenable to molecular genetics manipulations, making the study difficult. Here we report successful engineering of Chaeto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 64 publications
(117 reference statements)
5
58
0
Order By: Relevance
“…Similar oxidative coupling has recently been proposed for the biosynthesis of the related bis-spiro-azaphilone, cochliodone A. 25 …”
Section: Resultssupporting
confidence: 58%
“…Similar oxidative coupling has recently been proposed for the biosynthesis of the related bis-spiro-azaphilone, cochliodone A. 25 …”
Section: Resultssupporting
confidence: 58%
“…We chose to integrate cghA into the chaetoviridin biosynthetic PKS gene cazM [20] so that the integration event would be indicated by the loss of formation of chaetoviridin A 8 and B 9 . [19] A control experiment verified that disruption of cazM would not affect the production of 1 (Figure 4, i vs. ii). Comparison of the extract from the cghA -knockout strain and the cghA -complemented strain showed that the biosynthesis of 7 was no longer observed and exclusive production of 1 was restored with cghA (Figure 4, iii vs. iv), indicating CghA is directly responsible for ensuring the stereoselective formation of 1 and suppressing the nonenzymatic formation of the alternative stereoisomer, 7 .…”
mentioning
confidence: 84%
“…[17] Because the cgh gene cluster possessed an aldolase-coding cghB , we proposed CghB to catalyze the aldol condensation of two molecules of pyruvic acid to yield the intermediate 4 , which can then be stereoselectively transaminated to form 5 (Figure 1A). To test this hypothesis, we prepared 5 and its diastereomers chemoenzymatically [18] and used them in feeding experiments with an engineered C. globosum strain, CGKW14 [19] (Supporting Methods). After confirming the loss of production of 1 by ΔcghB /CGKW14 (Figure S14 i vs. iii), we fed 5 to this strain to observe the recovery of the production of 1 (Figure 2).…”
mentioning
confidence: 99%
“…This information was supported by the HMBC correlations from H[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and from H-8 to C-23, as well as the 1 H− 1 H COSY spin system of H 2 -20/H 2 -21/H 2 -22.…”
mentioning
confidence: 88%